Prognostic value of contralateral suppression on kidney function after surgery in patients with primary aldosteronism. (31st October 2022) - Voss, Nathalie; Mørup, Sara; Clausen, Caroline; Feltoft, Claus larsen; Jepsen, Jan Viberg; Hornum, Mads; Andreassen, Mikkel; Krogh, Jesper
Abstract: Background and objective : Adrenalectomy for primary aldosteronism (PA) has been associated with decreased kidney function after surgery. It has been proposed that elimination of excess aldosterone unmasks an underlying failure of the kidney function. Contralateral suppression (CLS) is considered a marker of aldosterone excess and disease severity, and the purpose of this study was to assess the hypothesis that CLS would predict change in kidney function after adrenalectomy in patients with PA. Design and patients : Patients with PA referred for adrenal venous sampling (AVS) between May 2011 and August 2021 and who were subsequently offered surgical or medical treatment were eligible for the current study. Results : A total of 138 patients were included and after AVS 85/138 (61.6%) underwent adrenalectomy while 53/138 (38.4%) were treated with MR‐antagonists. In surgically treated patients the estimated glomerular filtration rate (eGFR) was reduced by 11.5 (SD: 18.5) compared to a reduction of 5.9 (SD: 11.5) in medically treated patients (p = .04). Among surgically treated patients, 59/85 (69.4%) were classified as having CLS. After adrenalectomy, patients with CLS had a mean reduction in eGFR of 17.5 (SD: 17.6) compared to an increase of 1.8 (SD: 12.8) in patients without CLS (p < .001). The association between CLS and change in kidney function remained unchanged in multivariate analysis. Post‐surgery, 16/59 (27.1%) patients with CLS developed hyperkalemia compared to 2/26 (7.7%) in patients without CLS (p = .04).Conclusion : This retrospective study found that CLS was a strong and independent predictor of a marked reduction of eGFR and an increased risk of hyperkalemia after adrenalectomy in patients with PA. Summary: This study investigated the association between contralateral suppression, i.e., suppression of the nondominant adrenal gland, and the change in kidney function after surgery in patients with primary aldosteronism treated with adrenalectomy. We found that contralateral suppression was a strong and independent predictor of post‐surgical decline in eGFR.